Etude de paramètres de fonctionnement d'un sécheur des gaz associés : Groupement Bir Seba - الاخضر, داودي; رياض, بوخزنة; عبد الحق, رضواني (University of El-Oued, 2020)
"The presence of water in the gas has several problems during the treatment process as well as during transportation, to avoid these problems, we use several types of dryers to dehydrate the gas. After the phase of separating the oil and water from the associated gases, the gas passes through the dryer to eliminate as much as possible any trace of water that could cause hydrates in the equipment and facilities. The study we carried out on the process adopted at Bir Seba central processing facilities, by passing the gas under the effect of the current operating parameters, through the dryers so that the residual quantity of water in the gas will be less than 06 ppm with a dew point between (-57°C÷ -66°C), has shown that it is possible to reduce the drying time one (01) hour and therefore possibly make a saving in calorific energy consumed. " "يطرح وجود الماء في الغاز عدة مشاكل أثناء عملية المعالجة وكذلك أثناء النقل، ولتجنب هذه المشاكل نستخدم عدة أنواع من المجففات لتجفيف الغاز. بعد مرحلة فصل الزيت والماء عن الغازات المصاحبة، يمر الغاز عبر المجفف من أجل التخلص قدر الإمكان من أي أثر للماء يمكن أن يتسبب في تكوين الهيدرات في المعدات والمنشآت. الدراسة التي أجريناها على العملية المعتمدة في مركز إنتاج بئر السبع، بتمرير الغاز تحت تأثير معاملات التشغيل الحالية، من خلال المجففات بحيث تكون مستويات المياه المتبقية في الغاز أقل من 06 جزء في المليون ونقطة الندى بين (-57 درجة مئوية -66 درجة مئوية)، أظهرت أنه من الممكن تقليل وقت التجفيف بمقدار ساعة واحدة (01) وبالتالي من المحتمل الحصول على نقص في استهلاك الطاقة الحرارية. "
Keywords: gas, dehydration, molecular sieves, dryers. Hydrate; غاز، تجفيف، مناخل جزيئية، مجففات. هيدرات